Characterization of mycotoxins and microbial community in whole-plant corn ensiled in different silo types during aerobic exposure - Xia, Guang-hao; Huang, Yuan; Wu, Chang-rong; Zhang, Ming-zhu; Yin, Hai-yan; Yang, Feng; Chen, Chao; Hao, Jun (Frontiers in Microbiology, 2023)
Silage can be contaminated with mycotoxins and accidental fungi after aerobic exposure. The study assessed the effects of bunker silos (BS), round bales (RB), and silage bags (SB) on the nutritional characteristics, fermentation quality, aerobic stability, mycotoxin levels and microbial communities of whole-plant corn silage (WPCS). After 90 days of fermentation, silages were opened and sampled at 0, 1, 3, 5, 7, and 9 days of exposure. SB group conserved higher lactic acid and dry matter contents and a lower pH value than other groups after 9 days of exposure (p < 0.05). The SB group showed the longest aerobic stability (202 h) among all silages (p < 0.05). The concentrations of aflatoxin B1, trichothecenes and fumonisin B1 were significantly lower in SB after 9 days of exposure (p < 0.05). Acetobacter became the dominant bacteria in BS and RB groups after 5 days of exposure. However, Lactobacillus still dominated the bacterial community in SB group. Acetobacter was positively correlated with pH, acetic acid content, and ammonia-N content (p < 0.05). Lactobacillus was positively correlated with Kazachstania and Candida abundances (p < 0.01) but negatively correlated with Fusarium abundance (p < 0.05). Considering the feed value and food safety of silage in the feeding process, silage bags are recommended for WPCS according to the observed nutritional quality, fermentation index and mycotoxin content.